Validity and reliability of the Self-Care Scale for Adults (SCS-A): Indonesian version - Muhammad Luthfi Asysyidqi; Rinaldi Rinaldi (Universitas Ahmad Dahlan, 2026)
Self-care has been recognized as an important factor in maintaining physical and psychological well-being; however, validated instruments for assessing self-care in the Indonesian context remain limited. This study aimed to evaluate the validity and reliability of the Indonesian version of the Self-Care Scale for Adults (SCS-A). The original scale developed by Gómez-Ortiz et al. (2025) consists of nine items representing two dimensions: physical and psychological self-care. A total of 500 adults aged 18 years and above in Indonesia participated in this study. The adaptation process followed the International Test Commission guidelines (ITC, 2017) to ensure linguistic and conceptual equivalence. Content validity was assessed using Aiken’s V, with coefficients ranging from .89 to 1.00, indicating high levels of expert agreement. Construct validity was examined using confirmatory factor analysis (CFA), which demonstrated a good model fit (CFI=.960; TLI=.945; RMSEA=.078; SRMR=.043). Reliability analysis using Cronbach’s alpha yielded a coefficient of .881, indicating good internal consistency. Overall, the findings provide empirical support for the psychometric validity of the Indonesian version of the SCS-A. This instrument may be used to assess self-care among adults in Indonesia in both research and applied settings. Further validation across more diverse populations is recommended to strengthen its generalizability.